2010
DOI: 10.2174/157016210791111124
|View full text |Cite
|
Sign up to set email alerts
|

The Vpu Protein: New Concepts in Virus Release and CD4 Down-Modulation

Abstract: Human immunodeficiency virus type 1 (HIV-1) and several simian immunodeficiency viruses (SIV) encode for a transmembrane protein known as Vpu. While the smallest of the HIV-1 proteins, it has two important functions within virus-infected cells. The first of these functions is the down-regulation of the CD4 receptor to prevent its interaction with the HIV-1 envelope glycoprotein. Vpu interacts with the CD4 receptor in the rough endoplasmic reticulum (RER), resulting in its re-translocation across the RER and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 86 publications
3
40
0
Order By: Relevance
“…The derivation and pathogenicity of SHIV KU-1bMC33 and no vpu SHIV KU-1bMC33 have been described (McCormick-Davis et al, 2000; Singh et al, 2003; Stephens et al, 2002). The derivation of the SHIV KU-2MC4 Δvpu plasmid has been described (Ruiz et al, 2010). Vectors expressing the subtype B (pc vpuegfp ) and C Vpu (pcv pu sc egfp1 ) proteins fused to enhanced green fluorescent protein (eGFP) and the Vpu TM EGFP (pcv pu TM egfp ) mutant have been previously described (Singh et al , 2003; Gomez et al , 2005; Pacyniak et al , 2005; Ruiz et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The derivation and pathogenicity of SHIV KU-1bMC33 and no vpu SHIV KU-1bMC33 have been described (McCormick-Davis et al, 2000; Singh et al, 2003; Stephens et al, 2002). The derivation of the SHIV KU-2MC4 Δvpu plasmid has been described (Ruiz et al, 2010). Vectors expressing the subtype B (pc vpuegfp ) and C Vpu (pcv pu sc egfp1 ) proteins fused to enhanced green fluorescent protein (eGFP) and the Vpu TM EGFP (pcv pu TM egfp ) mutant have been previously described (Singh et al , 2003; Gomez et al , 2005; Pacyniak et al , 2005; Ruiz et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Viral protein U (Vpu) encoded by human immunodeficiency virus type I (HIV-1) augments viral pathogenesis by down-modulating CD4 molecules from the surface of infected cells and enhancing virion release (Fujita et al, 1997; Klimkait et al, 1990; reviewed in Ruiz et al, 2010; Schubert et al, 1998). Membrane association is critical for both activities although an earlier study indicated that the primary structure of the transmembrane domain was irrelevant for CD4 down-modulation (Schubert et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Vpu mediates the degradation of CD4 receptors [24,25] and enhances the release of progeny virions from virus-producer cells [26][27][28][29][30] by antagonizing the restriction to viral egress imposed by BST-2 [3,4,31]. Furthermore, counteraction of BST-2 by Vpu is important for HIV-1 pathogenesis in vivo [32][33][34], indicating that BST-2 is a functionally active restriction factor whose antagonism is required for the establishment of a successful infection in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Once inside the cell, the genetic material of the virus directs rapid and sustained downregulation of CD4 (26, 62), a phenomenon that promotes viral spread by preventing superinfection, enabling the release of progeny virions, and interfering with the host immune response (3,6,34,53). The ability of HIV-1 to downregulate CD4 depends on two accessory proteins encoded in the viral genome, Nef and Vpu (32,38,45,61). Nef is a myristoylated protein that attaches to the cytosolic leaflet of the plasma membrane, where it functions to link the cytosolic tail of CD4 to the clathrinassociated adaptor protein 2 (AP-2) complex (1,12,16,17,19,24,39).…”
mentioning
confidence: 99%